Multiuser MIMO downlink precoder design based on the maximal SJNR criterion - Yongle Wu; Jinfan Zhang; Mingguang Xu; Shidong Zhou; Xibin Xu (GLOBECOM '05. IEEE Global Telecommunications Conference, 2005, 2005)
In this paper, we aim to design a set of linear transmitter preceding vectors for the downlink of multiuser MIMO system, using the maximal signal to jamming and noise ratio (SJNR) criterion for each user, subject to a transmit power constraint. Unlike some conventional methods, the proposed scheme does not impose any restrictions on system configuration, i.e., the number of antennas at the transmitter and receivers. Furthermore, this new algorithm can mitigate the co-channel interference (CCI) and noise at the same time. Both analysis and simulation results have shown the superiority of the proposed method over conventional transmit precoders